The Effect of Exercise and Body Height on Leg Power of Extracurricular Participants at Islamic Junior High School Roudlotus Saidiyyah Semarang - Syahroni, Yusup; Rustiadi, Tri; Pramono, Harry (Journal of Physical Education and Sports, 2019)
The goal of this study is for knowing and analyzing: The difference on the effect of depth jump exercise and knee tuck jump exercise to the ability of leg power of students involved in extracurricular activity at Islamic Junior High School Roudlotus Saidiyyah Semarang, The difference of the effect of high and short of the body height to the leg power of students involved in extracurricular activity at Islamic Junior High School Roudlotus Saidiyyah Semarang, The interaction between the exercise method and body height to leg power of students involved in extracurricular activity at Islamic Junior High School Roudlotus Saidiyyah Semarang. This research is using the experimental method in applying the 2x2 factorial design plan. The data analysis technique is using Analysis of Varian (ANOVA) with 0.05 significance level (Î±). The dependent variable in this research is the method of depth jump exercise and knee tuck jump exercise. High and low body height is as the attribute variable and the dependent variable is the power legs. The results of the study are: (1) there is a difference on the effect of depth jump exercise and knee tuck jump exercise to the ability of leg power with significance level as (0.04) < Î± (0.05) and Fvalue = 7.027 > Ftable = 4.49, (2) there is a difference of the effect of high and short of the body height to the leg power whereas the significance = 0.030 < Î± = 0.05 and Fvalue = 5.317 > Ftable = 4.49, (3) there is an interaction between the exercise method and body height to leg power whereas the significance = 0.027 < Î± = 0.05 and Fvalue = 8.603 > Ftable = 4.49.